2019
DOI: 10.3389/fsurg.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation of Primary Malignant Pelvic Bone Tumors

Abstract: Background: En bloc tumor resection followed by reconstruction is a widely used surgical treatment for malignant pelvic bone tumors. High rates of complications and mechanical instability often contribute to poor postoperative results. We attempted en bloc microwave ablation (MWA) in situ to improve the outcome.Methods: From May 1995 to December 2015, 104 patients with primary pelvic malignancy received radical MWA in our department. After careful dissection of the tumor-bearing bone from surrounding normal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Pelvic osteosarcomas often are diagnosed later and with bigger volume than the ones occurring in long bones due to the fact that they are deeply located. To make it worse, pelvic osteosarcomas did not seem to respond well to neoadjuvant chemotherapy and the survival was more dismal than the ones in long bones ( 13 , 14 ). In fact, Guo et al suggested in one study that neo-chemotherapy does not seem to improve overall survival in pelvic osteosarcoma ( 15 ), which supported our decision to agree to discontinue neoadjuvant chemotherapy when the patient showed poor tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic osteosarcomas often are diagnosed later and with bigger volume than the ones occurring in long bones due to the fact that they are deeply located. To make it worse, pelvic osteosarcomas did not seem to respond well to neoadjuvant chemotherapy and the survival was more dismal than the ones in long bones ( 13 , 14 ). In fact, Guo et al suggested in one study that neo-chemotherapy does not seem to improve overall survival in pelvic osteosarcoma ( 15 ), which supported our decision to agree to discontinue neoadjuvant chemotherapy when the patient showed poor tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Human patients undergoing limb‐sparing procedures are faced with similar complications; however, improved complication rates were achieved in some studies when MWA was used. 34,35 Fan et al 34 evaluated 104 people with primary pelvic bone tumors that underwent MWA of the lesion followed by reconstruction with autograft or allograft and bone cement. In those human patients, the local recurrence was 8.6%, and the infection rate was 5.6%, which is lower than the recurrence rate (21% to 38%) and infection rate (21% to 28%) reported with surgical en bloc resection.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of adjacent soft tissues is maintained below 39°C. To treat the surgical margins in this pilot study, we placed the ablation probe so that the ablation zone would extend 1 to 2 cm beyond the margin of the tumor 22,23,34,35 . We placed the ablation probe to the most proximal aspect of the tumor in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that endoscopic MWA combined with BC can be performed through safe and short ablation cycles to control the diffusion of the heating zone without damaging vital nerves or blood vessels. Recently, Fan et al [28] attempted en bloc MWA in situ to improve the outcome of the treatment of primary malignant pelvic bone tumors, with encouraging oncological and functional results. Our results are consistent with those of previous studies, with immediate pain reduction and quality of life improvement obtained in almost 100% of the patients and maintained at the final follow-up visit.…”
Section: Discussionmentioning
confidence: 99%